For Tribal Farmers... Livelihood security through tubers - Nedunchezhiyan1, M.; Misra, R. S.; Mukherjee, A.; Sivakumar, P. Sethuraman (Indian Horticulture, 2019)
In hilly plateau regions of Chhattisgarh, Jharkhand and Odisha in India, cultivation of highyielding varieties of yam, yam bean, sweet potato, cassava and taro is promising. Root and tuber crops have played a significant role in improvement of livelihood of tribal farmers.